Impact assessment of front line demonstration of safflower on farmers’ fields: Impact assessment of front line demonstration of safflower on farmers’ fields - S A SHINDE; D P WASKAR; S B GHUGE; C V AMBADAKAR (Journal of Oilseeds Research, 2023)
AICRP on Safflower, VNMKV, Parbhani conducted 160 demonstrations on safflowers during Five consecutive years from 2017–18 to 2021–22. The critical inputs were identified in existing production technology through meetings and discussions with farmers. Uncontrolled weeds, ignorance about fertilizers and lack of plant protection measures, were the predominant identified causes of low productivity of safflower. The average results of Five years study revealed that the Seed yield under demonstration plots was 1290 Kg/ha as compared to 994 kg /ha in traditional farmer practices plots. The results clearly indicate the positive effects of FLDs over the existing practices. Percentage increase Seed yield over farmer practice was found 30%.